Association Between Diabetic Nephropathy Grade And Quality Of Life Among Saudi Type II Diabetic Patients In 2024 (The Review of Diabetic Studies, 2024)
Introduction: Diabetic nephropathy is one of the most severe long-term effects of diabetes mellitus. Diabetes has been shown to be the leading cause of end-stage renal disease in several nations.Aim of the work: analyze the association between diabetic nephropathy grade and quality of life among type II diabetic patients.Material and methods: Quantitative descriptive study design applied on a purposive sample of 41 individuals with type II diabetes attended to the medical outpatient clinic in Saudi Arabia Tools: Tool I- A structured interviewing questionnaire. Tool II- Assessment of the kidney function. Tool III- Kidney Disease Quality of Life.Results: serum creatinine and blood urea nitrogen were increased, also the estimated glomerular filtration rate (eGFR) was decreased in individuals with type II diabetes as disease duration increase. The prevalence of diabetic nephropathy in the current work was high representing 56.1%. In addition increasing body mass index more than 25. Diabetic nephropathy was associated with all five HRQOL dimensions as patients in stage 3-kidney disease had lower scores than patients in stages 1 and 2.Conclusion: The present data confirm that the most striking risk factors for diabetic nephropathy in the type II diabetes are BMI ≥ 25, diabetes duration, hypertension, age ≥ 50 years, and family history.Recommendation: The current study recommended that urinalysis should be performed regularly as part of a screening program which is a preventive intervention to preserve the kidneys in diabetic patients and will detect individuals with nephropathy early.